2005
DOI: 10.1111/j.1365-2036.2005.02683.x
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal fluid volumes and transit of dosage forms as assessed by magnetic resonance imaging

Abstract: SUMMARYAim: The gastrointestinal transit of sequentially administered capsules was investigated in relation to the availability of fluid along the intestinal lumen by magnetic resonance imaging. Methods: Water-sensitive magnetic resonance imaging was performed on 12 healthy subjects during fasting and 1 h after a meal. Specifiable non-disintegrating capsules were administered at 7, 4 and 1 h prior to imaging. Results: While food intake reduced the mean fluid volumes in the small intestine (105 ± 72 mL vs. 54 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
428
4
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 553 publications
(450 citation statements)
references
References 20 publications
(16 reference statements)
17
428
4
1
Order By: Relevance
“…The results indicate that the dissolution rate during a short time frame at locations near the dissolving surface may be more complex than regular effluent measurements would suggest. This is of relevance for situations where a dissolving surface may encounter non-sink conditions, for example during certain phases of its journey 575 through the gastro-intestinal tract, where it may encounter low fluid volumes (Schiller et al, 2005). Furthermore, the results suggest that a freely soluble excipient, such as LM, may affect the Page 27 of 40 A c c e p t e d M a n u s c r i p t 25 local hydrodynamic environment during dissolution testing of a low solubility active ingredient.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicate that the dissolution rate during a short time frame at locations near the dissolving surface may be more complex than regular effluent measurements would suggest. This is of relevance for situations where a dissolving surface may encounter non-sink conditions, for example during certain phases of its journey 575 through the gastro-intestinal tract, where it may encounter low fluid volumes (Schiller et al, 2005). Furthermore, the results suggest that a freely soluble excipient, such as LM, may affect the Page 27 of 40 A c c e p t e d M a n u s c r i p t 25 local hydrodynamic environment during dissolution testing of a low solubility active ingredient.…”
Section: Resultsmentioning
confidence: 99%
“…[6,7,212] The fluid volume in the small intestine is however not constant, for example it has been shown that it decreases by approximately 50% in fed vs fasted state. [215] On the other hand, many drug substances have poor solubility and/or low dissolution rate which means that the intestinal drug concentration may be overestimated. Other definitions for the intestinal drug concentration have been proposed by the FDA and EMA in their guidances on bioavailability and bioequivalence when classifying drug compounds into the biopharmaceutics classification system (BCS).…”
Section: Estimation Of the Intracellular Drug Concentrationmentioning
confidence: 99%
“…This work has been extended to the small bowel environment. MRI showed that liquid in the small bowel is present in discrete liquid "pockets" (Schiller et al, 2005); these have been quantified under conditions representing bioavailability/bioequivalence (BA/BE) studies at fasted baseline and after a 240 ml glass of water, using methods validated against naso-duodenal infusion (Hoad et al, 2007). The method is based on a heavily T2 (i.e.…”
mentioning
confidence: 99%
“…This has been done using 'transit capsule markers' filled with MRI-visible fluid. The imaging was based either on standard 1 H MRI Schiller et al, 2005) but also on 19 F MRI (Hahn et al, 2011(Hahn et al, , 2012(Hahn et al, , 2014, an interesting approach though the availability of the necessary hardware is scarce. The position of the MRI markers can be visualized and transit determined in a fashion similar to the radiological methods .…”
mentioning
confidence: 99%